1998
DOI: 10.1097/00006454-199804000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Ureaplasma urealyticum respiratory tract colonization is associated with an increase in interleukin 1-beta and tumor necrosis factor alpha relative to interleukin 6 in tracheal aspirates of preterm infants

Abstract: There were 18 positive cultures for U. urealyticum from 15 of 96 infants (15.6%). IL-1-beta in tracheal aspirates expressed as concentration per volume or as a ratio of IL-1-beta to IL-6 were 7- and 14.9-fold higher, respectively, in Ureaplasma-positive infants than in Ureaplasma-negative infants (P < 0.05). The TNF-alpha/IL-6 ratio was 18.9 and 15.5 times higher in the Ureaplasma-positive aspirates than in the Ure aplasma-negative aspirates on Day 1 and Days 7 to 10 (P < 0.05). Concentrations of IL-1-beta and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
53
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 47 publications
5
53
0
2
Order By: Relevance
“…Similarly, several authors have reported an increase in proinflammatory cytokines in infants who are colonized with U. urealyticum (23,24). Our study adds further to this literature by suggesting that in infants who do not have clinical or laboratory evidence of sepsis, U. urealyticum must be considered as an important contributor to acute lung injury, as was demonstrated by an increase of pro-inflammatory cytokines, particularly IL-6 and IL-8, which were both increased at birth in these infants.…”
Section: Discussionmentioning
confidence: 85%
“…Similarly, several authors have reported an increase in proinflammatory cytokines in infants who are colonized with U. urealyticum (23,24). Our study adds further to this literature by suggesting that in infants who do not have clinical or laboratory evidence of sepsis, U. urealyticum must be considered as an important contributor to acute lung injury, as was demonstrated by an increase of pro-inflammatory cytokines, particularly IL-6 and IL-8, which were both increased at birth in these infants.…”
Section: Discussionmentioning
confidence: 85%
“…Patterson et al 41 found significantly higher levels of interleukin-1␤ and tumor necrosis factor-␣ and significantly lower levels of interleukin-6 among infants colonized with U urealyticum on days 1 and 7 in comparison to noncolonized infants. Infants who ultimately developed CLD had significantly higher interleukin-1␤ and interleukin-1␤: interleukin-6 ratios.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Since inflammation is a fundamental pathologic feature of CLD, the genetic variants of cytokine genes may be good candidates to explain some of the individual variation in the development of this complication. TNF-a is a central mediator in the inflammatory cascade and TA concentrations are elevated in infants who develop CLD.…”
Section: Discussionmentioning
confidence: 99%
“…Increased concentrations of inflammatory mediators in airway secretions during the first week of life have been associated with the development of CLD in the preterm infant suggesting that inflammation plays a central role in this condition. [1][2][3][4][5][6][7][8] Concentrations of tumor necrosis factor-a (TNF-a), a central mediator in the inflammatory cascade, are elevated during the first week of life in the tracheal aspirates (TA) obtained from infants who subsequently develop CLD. 1,2 The magnitude of TNF-a production may be in part genetically determined.…”
Section: Introductionmentioning
confidence: 99%